Factors of risk to ealey childhood caries in a selected district in Sri Lanka - Shahim, F. N (My University, 2003)
The objective of this study was to determine the prevention of early childhood caries among children below five years in selected district in Sri Lanka.Further the tretment needs for erley childhood caries and the impact of early childhood caries on mothers was also assessed.ECC should be recognised as a priority health problem and dental service for children should be planned orgenized to be made availble and accessible to children below five years.Early screening of all children ,screening of pregnent mothers and health education programmes intergraded into the existing MCH services would be an effective method in reducing the prevelenace of ECC in Sri Lanka